Relationship between tissue hydroxyl radical and oxidatively modified macromolecule levels. Issue 2 (23rd July 2013) - Sasaki, Toru; Mogi, Sho‐Ichi; Kaneko, Takao; Kojima, Haruka; Katoh, Shinsuke; Sano, Akira; Kojima, Shuji
<x xml:space="preserve">Abstract</x> Aims The relationship between hydroxyl radical (·OH) and oxidatively modified macromolecule formations was examined in tissues from young and aged mice. Methods To determine the ·OH generation in tissues in vivo using the hydroxylation trapping reaction of ·OH into salicylic acid (SA), analytical conditions for dihydroxybenzoic acid (DHBA) and SA determination, and optimum dosages of SA for administration and time‐points of tissue sampling were determined. 2, 3‐DHBA levels in tissues from young mice and age‐related changes were determined with the oxidatively modified macromolecules. Results 2, 3‐DHBA, a hydroxylation compound of SA, is considered to be suitable for determination of ·OH levels in tissues. Tissue levels of 2, 3‐DHBA expressed as a molar ratio to SA, was comparable among tissues, and was in accordance with 8‐oxo‐2′‐deoxyguanosine (8‐oxodG) and carbonylated proteins. In the aging process, 2, 3‐DHBA levels in the brain and heart increased in the biphasic pattern in accordance with the 8‐oxodG and thiobarbituric acid reactive substances (TBARS) levels, whereas levels of carbonylated proteins were not changed with age. Conclusions An in vivo method for ·OH measurement using hydroxylation of SA was optimized. However, as a limitation, 2, 3‐DHBA, as well as other oxidative stress markers, could be affected by various in vivo factors. The accordance was seen among 2, 3‐DHBA, 8‐oxodG and carbonylated protein levels in tissues from young mice. The tissue levels of 2, 3‐DHBA increased in accordance with the 8‐oxodG and TBARS during the aging process. Geriatr Gerontol Int 2014; 14: 498–507.